Observation of Thickness-Dependent Exchange Interaction in EuO Ultrathin Films - Miyazaki, Hidetoshi; Hajiri, Tetsuya; Matsunami, Masaharu; Inukai, Manabu; Ito, Takahiro; Kimura, Shin-ichi (Frontiers in Nanotechnology, 2022)
The electronic structure of single crystalline EuO (100) ultrathin films, together with their exchange splitting energy (delta-E_EX) and ferro-magnetic phase transition temperature (TC), was investigated by temperature- and thickness-dependent angle-resolved photoemission spectroscopy. Both delta-E_EX and TC decreased monotonically with decreasing film thickness. The band shift showed an opposite thickness dependence at the  and X points, reflecting the balance of the hybridization between the Eu 4f and O 2p states (super-exchange interaction) and between the Eu 4f-O 2p and Eu 5d states (indirect-exchange interaction). The observed transition from an indirect energy gap in the bulk to a direct gap in the ultrathin films of the ferromagnetic semiconductor EuO could be potential in future spintronics devices.